The Role of After Sales Service on Customer Loyalty Mediated by Customer Satisfaction - Didit Haryadi; Haerofiatna Haerofiatna; Abdul Wahid Alfarizi (Komunitas Dosen Indonesia, 2022)
The development of technology which is increasingly advanced with time is a demand for the development of the times and increasingly complex human needs. This study, among others, examines and analyses the factors in increasing consumer loyalty to after-sales service through customer loyalty. This research was conducted at PT. Tunas Toyota Cilegon Banten with a population of 1102, then the sample used was 150 respondents. The questionnaire method was distributed using an interval scale of 1 strongly disagree to 10 strongly agree. The data analysis technique used SEM PLS. The results of this study indicate the effect of after-sales service on consumer loyalty, the influence of after-sales service on customer satisfaction, the influence of customer satisfaction on consumer loyalty, and customer satisfaction can be a mediation in increasing consumer loyalty.